2023
DOI: 10.1038/s41413-022-00239-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of TGF-beta3 in cartilage development and osteoarthritis

Abstract: Articular cartilage serves as a low-friction, load-bearing tissue without the support with blood vessels, lymphatics and nerves, making its repair a big challenge. Transforming growth factor-beta 3 (TGF-β3), a vital member of the highly conserved TGF-β superfamily, plays a versatile role in cartilage physiology and pathology. TGF-β3 influences the whole life cycle of chondrocytes and mediates a series of cellular responses, including cell survival, proliferation, migration, and differentiation. Since TGF-β3 is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 194 publications
2
47
0
Order By: Relevance
“…For instance, inhibiting TGF-β expression in synovial tissue could reduce synovial fibrosis in KOA ( Remst et al, 2014 ). However, given that TGF-β inhibits collagen deposition and is essential for preserving the homeostasis of the ECM environment, its absence will undoubtedly make it more difficult to maintain cartilage homeostasis in the knee ( Du et al, 2023 ). Thus, TGF-β is a double-edged sword.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, inhibiting TGF-β expression in synovial tissue could reduce synovial fibrosis in KOA ( Remst et al, 2014 ). However, given that TGF-β inhibits collagen deposition and is essential for preserving the homeostasis of the ECM environment, its absence will undoubtedly make it more difficult to maintain cartilage homeostasis in the knee ( Du et al, 2023 ). Thus, TGF-β is a double-edged sword.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoarthritis is a typical degenerative disease that affects whole joint tissues, including the cartilage layer, subchondral bone, menisci, and peripheral synovium. [60][61][62][63][64] Previous reports have focused on the key role of chemical factors to explain the occurrence and deterioration of OA. For example, upregulation of proinflammatory factors, including interleukins (ILs), tumor necrosis factors (TNFs), leukotrienes, and pain-related prostaglandin E2 (PGE2), has showed their high expressions with the progress of OA, leading to degradation of the entire joint tissues by activating hydrolases such as matrix metalloproteinases (MMPs).…”
Section: Discussionmentioning
confidence: 99%
“…[115] Biochemical factors including TGF𝛽s and bone morphogenetic proteins (BMPs) are revealed in the terminal differentiation of matured chondrocytes and the final osteophyte formation by endochondral ossification. [62,116,117] And importantly, Lee et al showed the interaction between chemical factor signaling and mechanical sensitive mediator, piezo1, could form a pathological feed-forward network to deteriorate OA, which indicated the mechanical transduction-triggered chemical events. [118] In our current study, we only showed the chondrocyte phenotype changes in response to ECM stiffening in the cartilage tissue of osteoarthritis mouse model (Figure 7), aiming to addressing the correlation between chondrocyte phenotype and ECM stiffening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TGF‐β3 maintains the balance between chondroblast differentiation and chondrocyte hypertrophy, and its regulatory role is particularly important in chondrogenesis. Recently, TGF‐β3 has been recognized as a potential therapeutic target for OA due to its protective effect by enhancing the recruitment of autologous MSCs to damaged cartilage (Du et al, 2023). Smads regulate chondrogenesis and MSC differentiation.…”
Section: Research On Bmsc‐mediated Ais Pathogenesismentioning
confidence: 99%